2023
DOI: 10.3389/fimmu.2023.1125737
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the study of myeloid-derived suppressor cells in infectious lung diseases

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature cells capable of inhibiting T-cell responses. MDSCs have a crucial role in the regulation of the immune response of the body to pathogens, especially in inflammatory response and pathogenesis during anti-infection. Pathogens such as bacteria and viruses use MDSCs as their infectious targets, and even some pathogens may exploit the inhibitory activity of MDSCs to enhance pathogen persistence and chronic infection of the host. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…In line with those findings, we found that long-term HDM exposure, as was used in the models in this study, increased both the number as well as the immunosuppressive activity of PMN- and M-MDSCs in the lung. Akin to the findings in murine asthma models, pulmonary viral infections, triggered by viruses such as influenza, have been reported to induce expansion of immunosuppressive pulmonary MDSCs in mice ( 10 , 18 ). In the asthma exacerbation model used in this study, long-term exposure to HDM was combined with a one-time exposure to IAV.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In line with those findings, we found that long-term HDM exposure, as was used in the models in this study, increased both the number as well as the immunosuppressive activity of PMN- and M-MDSCs in the lung. Akin to the findings in murine asthma models, pulmonary viral infections, triggered by viruses such as influenza, have been reported to induce expansion of immunosuppressive pulmonary MDSCs in mice ( 10 , 18 ). In the asthma exacerbation model used in this study, long-term exposure to HDM was combined with a one-time exposure to IAV.…”
Section: Discussionmentioning
confidence: 81%
“…An increasing body of evidence suggests that MDSCs play a crucial role in lung diseases such as lung cancer, chronic obstructive pulmonary disorder (COPD), tuberculosis, pulmonary hypertension, cystic fibrosis, pulmonary infection, and asthma ( 7 , 10 ). Our previous findings further underlined the important role of MDSCs in murine models of asthma ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, elevated levels of MDSCs have been observed in both blood and sputum of patients with active TB in studies, 338 and have also been induced in healthy individuals after exposure to Mtb 339 . These cells play a detrimental role in diminishing protective T‐cell responses and may contribute to the inability of hosts to eradicate the infection, which subsequently leads to the development of TB disease 340 . Tasquinimod, 341 an experimental quinoline‐3‐carboxamide, has demonstrated tremendous promise in inhibiting tumor growth in murine cancer models and has recently been shown to deplete MDSCs and reduce the relative bacterial burden in the lung and spleen of murine models of TB 342 (Table 2).…”
Section: Host‐directed Therapymentioning
confidence: 99%